FAKTOR PENDORONG DAN PENARIK TENAGA KERJA INDONESIA BERKERJA KE LUAR NEGERI (STUDI KASUS TKI YANG MELINTASI POS PEMERIKSAAN LINTAS BATAS ARUK SAMBAS) - B01112062, Aziandi (Jurnal Curvanomic, 2017)
Abstract This research aims to find out about the characteristics and factors the effect the Indonesian Workers (TKI) to work overseas and enter through the Cross Border Inspection Post (PPLB) of Aruk, Sambas District. This study used primary data obtained through questionnaires and interviews with purposive sampling of 100 respondents. The analytical tool used in this research was multiple regression. The independent variables are age, education level, number of dependents, and respondents’wage, while the dependent variable used is the lenght of work. The characteristics of Indonesian workers who crossed PPLB of Aruk Sambas were dominated by the productive workers of 23-29 years of age (39 percent), with elementary education below (56 percent), with 0-2 dependent (49 percent), with wages < RM.1200 (76 percent). In addition, the results of multiple regresssion analysis show that the factors that significantly affect the workers’length working abroad who crossed PPLB of Aruk Sambas is age. Meanwhile, the level of education, number of dependents, respondents’wage had no significant effect. Keywords: leng of work, age, education level, number of dependent and wages